2019
DOI: 10.1109/tdsc.2019.2931557
|View full text |Cite
|
Sign up to set email alerts
|

Sonification to Support the Monitoring Tasks of Security Operations Centres

Abstract: Sonification (the representation of data as sound) may offer a solution to some of the network-security monitoring challenges faced in security operations centres (SOCs). Prior work has shown that sonification can present network-security information to humans effectively, and indicated that security practitioners foresee potential for sonification to aid in scenarios related to their work. The use of sonification by security practitioners in tasks relevant to SOCs has not been examined, however. To address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Iqbal & Anwar [19] and Islam et al [20] utilized the machine learning approach that enable rapid detection and automates alert for immediate response to identify threat. The SOC is supported by the advanced technology tools such as the Security Information and Event Management (SIEM) system, intrusion detection/prevention system (IDS/IPS), advanced threat intelligence and forensic analysis tools as defense mechanism, protect organizations from the potential damage caused by threats [21], [9], [22], [23], [8].…”
Section: Related Workmentioning
confidence: 99%
“…Iqbal & Anwar [19] and Islam et al [20] utilized the machine learning approach that enable rapid detection and automates alert for immediate response to identify threat. The SOC is supported by the advanced technology tools such as the Security Information and Event Management (SIEM) system, intrusion detection/prevention system (IDS/IPS), advanced threat intelligence and forensic analysis tools as defense mechanism, protect organizations from the potential damage caused by threats [21], [9], [22], [23], [8].…”
Section: Related Workmentioning
confidence: 99%
“…Besides the approaches to audiovisual data analysis described in the previous sections of this report, audiovisual monitoring interfaces play an integral role in various domains, including air traffic control [EBL*23], control rooms [SFLD22, HHG*12], anesthesia [AQH*21,RMS*22], neurology [LCS*28], dermoscopy [WRK*19], surgery [Zie23], network monitoring [Wor19a,AHvR*21], automotive [JDS15,XWX*22], to name a few.…”
Section: Adjacent Topicsmentioning
confidence: 99%
“…Starting 2018, increasing interest in sonification and its potential for SOCs can be identified [165] as it was implemented within the SIEM system of a SOC [166]. This showed that humans can detect attacks by listening to network traffic [127], [167] in specific contexts [168].…”
Section: ) Presentationmentioning
confidence: 99%